Mammie Apples, Trinidad - (:unkn) unknown (Stephens Ltd., Trinidad, 2009)
A picture of a bunch of Mammy Apples (Mammea americana, L.) on a branch. The diameter of Mammy apples range from 10 to 20 cm. When unripe, the fruit is hard and heavy. When fully ripe the flesh is slightly soft. Beneath the skin, there is a white, dry membrane. The flesh is orange or yellow, not fibrous, and can have various textures (crispy or juicy, firm or tender). Generally the smell of the flesh is pleasant and appetizing. Small fruits contain a single seed, while larger ones might have up to four. The seeds are brown, rough, oval and around 6 cm long. The juice of the seed leaves an indelible stain.
Colour: Coloured; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Fruit--Trinidad and Tobago; Tropical fruit--Trinidad and Tobago